EFFECT FORMING FACTORS IN THE LOGISTICS SYSTEM AFFECTING THE STRATEGY INVENTORY MANAGEMENT ENTERPRISE - Pshinko, O. M.; Koretska, S. O.; Chebotenko, V. O. (Science and Transport Progress, 2005)
The paper studies the main regularities and tendencies of raising efficiency of the company’s material stocks management on the basis of logistical concept and presents the main provisions of the logistical concept of managing the material stocks in the logistical system. The effect-creating factors in the logistical system have been revealed, influencing the strategy of the material stocks management.